Cisza . The Silence (Andrzej Wajda Master School of Film Directing, 2004)
A set of six short episodes made during the first documentary course in the Wajda School, depicting various faces of silence - the frightening silence of a new born baby before the first cry, the bored (or perhaps, pensive) silence of Roman Polański presidingat the press-conference, the solemn silence of the funeral ceremony, etc.